2012
DOI: 10.1111/j.1478-5153.2012.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective audit of a nurse independent prescribing within critical care

Abstract: These findings could be used to inform research and role development within the critical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…This may reflect the extent of the medication safety resources employed within critical care (e-prescribing, specialist critical care pharmacist 7 days/week, extensive critical care guidelines, education sessions, robust and responsive clinical incident reporting system)16 and use of advanced nurse practitioners 17…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect the extent of the medication safety resources employed within critical care (e-prescribing, specialist critical care pharmacist 7 days/week, extensive critical care guidelines, education sessions, robust and responsive clinical incident reporting system)16 and use of advanced nurse practitioners 17…”
Section: Discussionmentioning
confidence: 99%
“…Carberry et al . () conducted a short prospective audit in three ICUs of all prescriptions made by three groups, trainee medical staff, advanced nurse practitioners in critical care (ANPCC) and consultants, over 7 days. They examined error rates between the three groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pirret also found that she prescribed a wider range of medications when authorized to prescribe, with significant increases in diuretics, antiarrhythmics, intravenous fluids and antibiotics. Carberry et al (2012) conducted a short prospective audit in three ICUs of all prescriptions made by three groups, trainee medical staff, advanced nurse practitioners in critical care (ANPCC) and consultants, over 7 days. They examined error rates between the three groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The consensus process also highlighted interventions that the pharmacists thought less important or less proven in terms of critical care medication safety. The removal of nurse and pharmacist (All) prescribers after Round 1 and pharmacist prescribers (Advanced) after Round 2 suggest that more research needs to be carried out to understand the effect of non‐medical prescribers on medication errors in critical care patients . For example, we have recently reported that clinical pharmacists demonstrated a high degree and wide‐ranging scope of prescribing activity in general critical care patients with a very low error rate .…”
Section: Discussionmentioning
confidence: 99%